Mass Higher Education Development in East Asia
XIX, 371 p. 52 illus., 39 illus. in color.
Keywords: This book discusses mass higher education development in East Asian countries by means of three main issues: the strategy for higher education development; the way professors and students in the region are experiencing the rapid developments; and the challenges imposed by mass higher education. These challenges include the quality of education as well as structural changes in the rapidly developing systems, funding sources for supporting mass higher education, and job markets for college graduates. "… This is by far the best book so far produced on the building of higher education in Asia and brings forward our understanding of issues and problems everywhere of rapid educational growth, the economic costs and contributions of education, capacity building in the academic profession and science, and lifting quality…" — Simon Marginson, Professor of Higher Education, Institute of Education, University College London and Joint Editor-in-Chief of the journal Higher Education “Higher education is the new ‘coin of the realm.’… This book outlines what is happening in a key region of the world. The authors are at the ‘top of their game’ and able to offer us breaking trends with trenchant analysis.” — William G. Tierney, University Professor & Co-director, Pullias Center for Higher Education, University of Southern California "… East Asia came to the "mass revolution" after North America and Europe, but has been deeply affected by it. This book provides an excellent multidimensional analysis of the key elements of massification as they affect this key region." — Philip G. Altbach, Research Professor and Director, Center for International Higher Education, Boston College. “Mass Higher Education Development in East Asia is a well-researched book, bringing together an impressive group of renowned academics from the East and the West who offer a balanced assessment of the achievements and challenges in East Asian higher education…” — Jamil Salmi, Global Tertiary Education Expert, former World Bank Tertiary Education Coordinator.